Experienced EFL teachers switching to online teaching: A case study from China. (April 2022) - Yan, Chunmei; Wang, Li
Abstract: Despite the growth of studies on technology-enhanced language education, language teachers' experiences and stages of transiting to teach online during crisis have received little attention. Informed by the boundary-crossing learning theory as a theoretical framework, this case study aimed to examine three experienced Chinese junior secondary school English teachers' transition to teaching online as a result of the school closure during the outbreak of COVID-19. In the study, we collected a variety of data from the participants including their narratives through stimulated recalls about teaching online, teaching artifacts (e.g., worksheets, lesson plans) about their instructional features, and semi-structured interviews about the transitional process. Reflexive thematic analysis was followed to construct understandings about the participants' online teaching experiences and influencing factors. The results show that the participants experienced three stages of online shift, involving preparing, adapting and stabilizing stages facilitated by four dialogical learning mechanisms, i.e., identification, coordination, reflection and transformation. Their dispositional traits and proactive efforts, and systemic support contributed to their process of overcoming pedagogical, technical and emotional challenges during the boundary-crossing process. Implications are drawn on strategies that facilitate language teachers' emergency online teaching, and professional development for better online delivery. Highlights: This multiple case study documents three experienced Chinese EFL teachers' emergency online switching during the Covid-19 pandemic. The boundary crossing theory was employed as theoretical framework. Data was collected from semi-structured interviews, teachers' reflective narratives, online classroom observations and teaching artifacts. The teachers underwent three challenging stages to ensure students' online engagement and learning outcomes, which were facilitated by four learning mechanisms. The teachers' online switching was found to be attributed to the synergistic effects of their personal traits and efforts, and the systemic strong support from all levels.